Blood donation for iron removal in individuals with HFE mutations: study of efficacy and safety and short review on hemochromatosis and blood donation - Infanti, Laura; Leitner, Gerda; Moe, Morten; Pehlic, Vildana; Cattaneo, Marco; Benkert, Pascal; Holbro, Andreas; Passweg, Jakob; Worel, Nina; Buser, Andreas (Frontiers in Medicine, 2024)
Background Elevated serum ferritin with/without HFE variants in asymptomatic persons leads frequently to referral for blood donation. Hemochromatosis (p.C282Y/p.C282Y) only requires treatment. We evaluated safety and feasibility of iron removal in healthy persons with elevated ferritin and HFE variants using blood donation procedures. Materials and methods Thirty subjects with ferritin >200 ng/mL (women) or >300 ng/mL (men) with p.C282Y/p.C282Y, p.C282Y/p.H63D or p.H63D/p.H63D were randomized to weekly phlebotomy (removal of 450 mL whole blood) or erythrapheresis (removal of 360 mL red blood cells) every 14 days. The ferritin target was <100 ng/mL. A full blood count and ferritin were measured at each visit. Hemoglobin (Hb) ≥140 g/L was required at inclusion. If Hb dropped to <120 g/L (women) or <130 g/L (men), procedures were postponed (7 or 14 days). Primary endpoint was the number of procedures needed to the ferritin target; secondary objectives were duration of treatment and compliance. The treatment effect was tested with Poisson regression; number of procedures and treatment duration were compared between study arms with the Kruskal–Wallis test. Results Twenty-five of 30 participants were men (83%); mean age was 47 years (SD 10.5), mean BMI 26.6 kg/m2 (SD 3.6); 17 had p.C282Y/p.C282Y, nine p.C282Y/p.H63D, four p.H63D/p.H63D. Median baseline Hb was 150 g/L (IQR 144, 1,559), median ferritin 504 ng/mL (IQR 406,620). Twenty-seven subjects completed the study. Treatment arm (p < 0.001) and HFE variant (p = 0.007) influenced the primary endpoint significantly. To ferritin levels <100 ng/mL, a median number of 7.5 (IQR 6.2, 9.8) phlebotomies and 4.0 (IQR 3.0, 5.8) erythraphereses (p = 0.001) was needed during a median of 66.5 days (IQR 49,103) and 78.5 days (IQR 46139), respectively (p = 0.448). Low Hb was the principal reason for protocol violation; anemia occurred in 13 participants (48%). Immediate complications were infrequent; fatigue was reported after 25% of phlebotomies and 45% of erythraphereses. Thirty-five procedures were postponed because of low Hb and 15 for non-medical reasons. The median interval was 7.0 (IQR 7.7) and 14.0 (IQR 14, 20) days between phlebotomies and erythraphereses, respectively. Conclusion Blood donation procedures remove iron effectively in HC, but frequent treatments cause Hb decrease and fatigue that can impair feasibility.